Prevalence, Management, and Outcomes of Spinal Cord Injury from Spinal Tumors A Cross-Sectional Clinical Study - Rauf Memon, Aurangzeb Kalhoro, Sanaullah Pathan, Muhammad Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Spinal cord injuries (SCIs) secondary to spinal tumors are a significant cause of morbidity, often leading to irreversible neurological deficits and reduced quality of life. Despite advancements in diagnostic imaging and surgical interventions, there is limited local data on the prevalence, treatment approaches, and clinical outcomes associated with spinal tumor-related SCIs. Objective: To evaluate the prevalence, management strategies, and clinical outcomes of spinal cord injuries caused by spinal tumors among patients presenting to a tertiary care center. Methodology: This cross-sectional clinical study included 83 patients diagnosed with spinal cord injury due to spinal tumors between June 2022 and June 2023 at Liaquat University of Medical and Health Sciences, Jamshoro, Pakistan. Data were collected on patient demographics, tumor location and type (benign vs. malignant), neurological deficits, diagnostic modalities, treatment interventions (surgical decompression, radiotherapy, chemotherapy), and post-treatment outcomes. Functional status was assessed using the ASIA Impairment Scale and Modified Barthel Index before and three months after treatment. Results: The prevalence of spinal cord injury from spinal tumors was highest in patients aged 45–65 years (56.6%), with a male predominance (61.4%). Thoracic spine involvement was most common (48.2%), and 62.7% of tumors were malignant. Surgical decompression was performed in 53% of patients, followed by adjuvant radiotherapy and/or chemotherapy. Neurological improvement was observed in 39.7% of cases, while 25.3% had no change and 10.8% deteriorated. Functional independence significantly improved in surgically treated patients (p < 0.05). Conclusion: Spinal cord injuries from spinal tumors remain a challenging clinical entity, with a high burden of neurological deficits and variable recovery outcomes. Early diagnosis and timely surgical intervention are key to optimizing functional recovery and reducing long-term disability. Keywords: Spinal cord injury, spinal tumors, neurological outcome, surgical decompression, functional recovery, cross-sectional study.